Apremilast for oral ulcers associated with active Behcet's syndrome over 68 weeks: long-term results from a phase 3 randomised clinical trial - (:unkn) unknown (CLINICAL & EXPER RHEUMATOLOGY, 2021)
Objective. This study assessed the efficacy and safety of apremilast for the oral ulcers associated with Behcet's syndrome (BS) up to 64 weeks. Methods. The phase 3, double-blind, placebo-controlled RELIEF study randomised adult patients with active BS to placebo or apremilast 30 mg twice daily for 12 weeks, followed by an extension phase with all patients receiving apremilast through Week 64 and 4-week post-treatment follow-up (upon treatment discontinuation). The primary endpoint was area under the curve for the number of oral ulcers over 12 weeks (AUCWk0-12), reflecting the number of oral ulcers over time and accounting for their recurring-remitting course. Oral ulcer number, complete and partial responses, pain and disease activity and quality of life (QoL) were also assessed throughout the study. Results. A total of 207 participants were randomised and received at least one dose of study medication; 178 entered the extension phase and 143 completed Week 64. AUCWk0-12 was significantly lower with apremilast versus placebo (p<0.0001), and oral ulcers number, pain, complete/partial responses, disease activity and QoL with apremilast versus placebo showed improvements at Week 12, which were maintained through Week 64. The most common adverse events were diarrhoea, nausea, headache and upper respiratory tract infection; no new safety concerns were observed with longer-term apremilast exposure. Conclusion. In patients with oral ulcers associated with BS, apremilast was efficacious and benefits were sustained up to 64 weeks with continued treatment. Apremilast was well tolerated, and safety was consistent with its known safety profile.
Keywords: Behcet's syndrome; long-term treatment; phosphodiesterase 4 inhibitor; quality of life; oral ulcers; PHOSPHODIESTERASE-4 INHIBITOR; PSORIATIC-ARTHRITIS